2011
DOI: 10.1128/jcm.00535-11
|View full text |Cite
|
Sign up to set email alerts
|

Adamantane- and Oseltamivir-Resistant Seasonal A (H1N1) and Pandemic A (H1N1) 2009 Influenza Viruses in Guangdong, China, during 2008 and 2009

Abstract: Adamantane and oseltamivir resistance among influenza viruses is a major concern to public health officials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
10
1
Order By: Relevance
“…Our data revealed the disproportional levels of amantadine resistance observed in H5N1 viruses and human seasonal H3N2 and H1N1pdm09 viruses in recent years (Deybe et al, 2007; Zaraket et al 2010; Zhou et al, 2011). Importantly, the susceptibility of H5N1 influenza viruses to amantadine has increased in recent years (2010–2012).…”
Section: Discussionmentioning
confidence: 63%
“…Our data revealed the disproportional levels of amantadine resistance observed in H5N1 viruses and human seasonal H3N2 and H1N1pdm09 viruses in recent years (Deybe et al, 2007; Zaraket et al 2010; Zhou et al, 2011). Importantly, the susceptibility of H5N1 influenza viruses to amantadine has increased in recent years (2010–2012).…”
Section: Discussionmentioning
confidence: 63%
“…The prevalence of oseltamivir resistance among seasonal H1N1 viruses increased to almost 100% during 2009-2010, even in countries where oseltamivir had not been used [8]. Of note, although most oseltamivir-resistant seasonal H1N1 viruses were adamantane-susceptible, a number of seasonal H1N1 viruses resistant to both oseltamivir and adamantanes was detected in 2009 in several countries [9,10].…”
Section: Infection With Influenza Viruses Including Seasonal Avian mentioning
confidence: 99%
“…10 Some studies have reported the resistance pattern of the H1N1 09 virus to amantadine and oseltamivir. [11][12][13] Rapid detection of such resistance is clinically important in reducing the time between diagnosis and initiation of individualized therapy. Therefore, close monitoring of the prevalence of antiviral resistance and discoveries of drugs and potent vaccines are necessary to control influenza burden.…”
Section: Viral Culturementioning
confidence: 99%